Pengembangan Proses Pembelajaran Matematika Kurikulum 2013 Berbasis Lesson Study Pada Siswa Kelas Viii Smp Negeri 1 Salatiga Tahun 2015/2016 - Suprapto, Mar'atus Sholeha Yulia, Prof. Dr. Sutama, M.Pd (2017)
The learning process is inseparable from the learning activities and become something very important. To obtain optimal results mathematics learning, the learning process will be the development of mathematics curriculum based lesson Study.Penelitian 2013 aims to 1) analyze and describe the process of learning mathematics curriculum-based lesson study 2013 grade 8, 2) analyze and test the products that will be developed grade 8 in SMP Negeri 1 Salatiga, 3) analyze and test the effectiveness of the products to be developed in SMP Negeri 1 salatiga.Jenis research research and development (R & D) with the design of research studies using data collection research evaluatif.Tehnik yamg used is documentation, interviews, observation, tests and focus group data using triangulation Discussion.Tehnik keabsaan trianguasi sources and techniques. Qualitative data analysis techniques using flow analysis and comparative method. The results of research and development are 1) Mathematics learning process carried out by school teachers Salatiga there are three phases of learning that preliminary activities, the core activities and closing activity, 2) Development of the process of learning mathematics curriculum-based Lesson Study 2013 Class VIII SMP Salatiga performed on core activities and 3) Effectiveness of the learning process of mathematics curriculum in 2013 based lesson study has increased for the better, from the aspect of the students' motivation to complete the task on time, aspects of self-learning, aspects of the student to provide a conducive learning aspects of student involvement in filing question, aspects of student involvement in solving problems.